A cross-sectional study on phlebotomine sand flies in relation to disease transmission in the Republic of Kosovo - Xhekaj, Betim; Hoxha, Ina; Platzgummer, Katharina; Stefanovska, Jovana; Dvořák, Vít; Milchram, Markus; Obwaller, Adelheid G; Poeppl, Wolfgang; Muja-Bajraktari, Nesade; Walochnik, Julia; Trájer, Attila J; Sherifi, Kurtesh; et al. (Medical and veterinary entomology, 2024)
Sand flies (Diptera: Psychodidae: Phlebotominae) are blood-feeding insects that transmit the protozoan parasites Leishmania spp. and various arboviruses. The Balkan region, including the Republic of Kosovo, harbours a diverse sand fly fauna. Vector species of Leishmania infantum as well as phleboviruses are endemic; however, recent data are scarce. We performed a cross-sectional study to update the current sand fly distribution in Kosovo and assess biological as well as environmental factors associated with sand fly presence. CDC light trapping was conducted at 46 locations in 2022 and 2023, specifically targeting understudied regions in Kosovo. Individual morphological species identification was supported by molecular barcoding. The occurrence data of sand flies was used to create distribution maps and perform environmental analyses, taking elevation, wind speed and climate-related factors into account. In addition, PCR-based blood meal analysis and pathogen screening were conducted. Overall, 303 specimens of six sand fly species were trapped, predominated by Phlebotomus neglectus (97%). Barcodes from eight of nine known endemic sand fly species were obtained. Combining our data with previous surveys, we mapped the currently known sand fly distribution based on more than 4000 specimens at 177 data points, identifying Ph. neglectus and Ph. perfiliewi as the predominant species. Environmental analyses depicted two geographical groups of sand flies in Kosovo, with notable differences between the species. In total, 223 blood meals of five sand fly species were analysed. Of seven identified host species, the predominant blood meal source was observed to be cattle, but the DNA of dogs and humans, among others, was also detected. This study assessed biological as well as ecological factors of sand fly occurrence, which should help better understand and evaluate potential hot spots of disease transmission in Kosovo.
Keywords: průřezové studie; Psychodidae; Insect Vectors; Cross-Sectional Studies; psi; Animal Distribution; Male; Animals; Leishmania infantum; Female; mužské pohlaví; ženské pohlaví; Kosovo; hmyz - vektory; rozšíření zvířat; zvířata; Dogs; Phlebotomus